Ab initio MCDHF calculations of electron–nucleus interactions. (30th April 2015) - Bieroń, Jacek; Fischer, Charlotte Froese; Fritzsche, Stephan; Gaigalas, Gediminas; Grant, Ian P; Indelicato, Paul; Jönsson, Per; Pyykkö, Pekka
Abstract: We present recent advances in the development of atomic ab initio multiconfiguration Dirac–Hartree–Fock theory, implemented in the GRASP relativistic atomic structure code. For neutral atoms, the deviations of properties calculated within the Dirac–Hartree–Fock (DHF) method (based on independent particle model of an atomic cloud) are usually dominated by electron correlation effects, i.e. the non-central interactions of individual electrons. We present the recent advances in accurate calculations of electron correlation effects in small, medium, and heavy neutral atoms. We describe methods of systematic development of multiconfiguration expansions leading to systematic, controlled improvement of the accuracy of the ab initio calculations. These methods originate from the concept of the complete active space (CAS) model within the DHF theory, which, at least in principle, permits fully relativistic calculations with full account of electron correlation effects. The calculations within the CAS model on currently available computer systems are feasible only for very light systems. For heavier atoms or ions with more than a few electrons, restrictions have to be imposed on the multiconfiguration expansions. We present methods and tools, which are designed to extend the numerical calculations in a controlled manner, where multiconfiguration expansions account for all leading electron correlation effects. We show examples of applications of the GRASP code to calculations of hyperfine structure constants, but the code may be used for calculations of arbitrary bound-state atomic properties. In recent years it has been applied to calculations of atomic and ionic spectra (transition energies and rates), to determinations of nuclear electromagnetic moments, as well as to calculations related to interactions of bound electrons with nuclear electromagnetic moments leading to violations of discrete symmetries.